A bright future : how some countries have solved climate change and the rest can follow - Goldstein, Joshua S., 1952-; Qvist, Staffan A (Public Affairs, 2019)
"A proven, fast, inexpensive, practical way to cut greenhouse gas emissions and prevent catastrophic climate change. As climate change nears potentially disastrous tipping points, a solution is hiding in plain sight. Several countries have successfully replaced fossil fuels with low-carbon energy sources by combining renewable energy with a quick buildout of nuclear power. By following their example, the world could dramatically cut fossil fuel use by midcentury, even as energy consumption continues to rise. Joshua Goldstein and Staffan Qvist explain how clean energy rapidly replaced fossil fuels in such places as Sweden, France, and Ontario, while enhancing both prosperity and the natural environment. Engagingly written, yet backed by deep research, this book will encourage a fresh look at the assumptions that have long shaped the climate change debate. The stakes are extraordinarily high and the deadline for action is near. This clear and compelling book could spark the transformation in energy policy that the world needs."--Dust jacket.